Care in chaos : frustration and challenge in community care - Hadley, Roger. 1931-2001.; Clough, Roger (London ; New York : Cassell, 1996)
This challenging book focuses on the impact of the recent major 'reforms' in community care. There is growing evidence that the reforms are failing, but a perspective culture of secrecy and conformity in the health and social services prevents practitioners from speaking out openly about what is happening.
In this book, under the protection of anonymity, practitioners from statutory, voluntary and private organizations talk freely about their experiences. Their witness provides a devastating criticism of the way the community care changes have been implemented and of the debilitating limitations imposed on good practice. The authors analyse the fundamental weaknesses in policy revealed in these interviews and propose a positive and realistic alternative.
Care in Chaos will be indispensable for all doctors, social workers, nurses, care workers, carers, managers, policy makers, students and others who are concerned with community care.
Includes bibliographical references p. 212-215 and index.
Keywords: Public welfare -- Great Britain; Human services -- Great Britain; Great Britain -- Social policy -- 1979-; Great Britain -- Social conditions -- 1945-